Prawo sędziowskie na Węgrzech - Visegrády, Antal (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
Currently, there is a big discussion about judicial activism in continental legal systems. This phenomenon is rather negatively described, as the breaking the fundamental principle of separation of powers. In this paper, it will be demonstrated that, although Hungary belongs to civil law system, where judges are not allowed to be a lawmakers, actually they do make law. In Hungarian law, there is a great number of cases when judges evidently make law. What is more, their activism has a very positive impact on the whole legal system; judges make law more just and uniform, and at the same time enhance its certainty. In the following parts of the paper, it will be described the lawmaking role of judges, particular inlegal fields such as: civil law, criminal law, labor law etc.